Thematic Unity in the Holy Qur’an and the Delusions of the Orientalists - Al-Ghool, Shadi Mohammed (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to provide a realistic description of the unity of the Quranic surah, and to explain the difference between the idea of thematic unity and textual coherence in the Qur’an. To achieve the aims, two problems shall be clarified. The rationality of the Orientalists’ views of the thematic unity in the Qur’an, and the possible connection between the orientalists’ views on Arabic poetry and their views on the Qur’an. Methods: The study adopts a descriptive methodology, which relies on studying the views of Orientalists based on scientific principles. Results: This study proves the invalidity of the thematic unit study in Arabic poetry and the Quranic text in particular. It also highlighted the dangers of affirming or denying it within the Quranic surahs. The Western concept of affirming unity would be burdensome, especially in longer surahs, and could diminish the coherence and completeness of the surah. Conversely, denying unity in the surah would be a flaw in the Quran’s elevated literary style, resulting in inconsistency and deficiency. Conclusions: This study evaluates a comprehensive and detailed description of the views of Orientalists on the thematic unity of the Quran, in order to draw a realistic picture of describing the Qur’an with its contextual connection, and fulfilling the condition of textuality. It proves that the multiplicity of topics in one Quranic surah is not offensive in connection and harmony of the Quranic text.